Bullous Pemphigoid in a Renal Transplant Recipient, A Case Report and Review of the Literature (Iranian Journal of Kidney Diseases, 2020)
Bullous pemphigoid (BP) is an autoimmune disease with chronic, recurrent bullous eruptions. BP has been reported to be associated with drugs, physical stimuli, malignancies, and immune abnormalities. Its association with renal transplant is rare and only 12 cases have been reported until now. We present a case of BP in a 33-year-old man with history of bladder exstrophy from birth and renal transplantation from 5 years ago. There was no finding in favour of his disease was caused by graft rejection, drug usage, or viral infection. Therefore, BP could be an accidental finding in this patient with idiopathic aetiology.